Geoecological analysis and assessment of the Chernihiv region territory - Барановська Ольга; Барановський Микола (Київський національний університет імені Тараса Шевченка, 2021)
The main purpose of the geoecological research of Chernihiv region is a comprehensive analysis and assessment of the ecological state of geosystems in terms of human needs. Based on the analysis of natural features of geosystems of Chernihiv region and their geochemical properties, differences in self-cleaning ability of landscapes were revealed. The relatively high potential for removal of hazardous substances is peculiar to the elevated dissected landscapes of the southeastern and northeastern parts of the region. The landscapes of the Dnieper and Desna Polissya and the Northern region of the Dnieper terrace plain account for the greatest share of areas with low potential for pollutants removal. Anthropogenic impact on the environment of Chernihiv region is quite significant and diverse in type, intensity, and territorial distribution. The consequences of this impact are radioactive contamination of the western and northeastern parts of the region, high level of air pollution in cities, unsatisfactory ecological state of groundwater, especially in Chernihiv Polissya, degradation of land resources. Based on the analysis of the ecological state of individual natural components, the integrated indicator of pollution of geosystems of the administrative districts (as of the year 2019) of Chernihiv region was determined and its western and northeastern territories are defined to have the most severe ecological situation in the region. As a result of a correlation analysis between the indicators of environmental pollution of Chernihiv region and the state of public health, it was found that the radioactive contamination of the territory by 137Cs has the greatest influence on the morbidity of the region’s population. It causes high incidence rates of the endocrine system, blood and hematopoietic organs diseases. This feature should be considered when developing environmental policy of the region.

Основною метою геоекологічного дослідження Чернігівської області є всебічний аналіз і оцінка екологічного стану геосистем з погляду потреб людини. На основі аналізу природних особливостей геосистем Чернігівщини, їхніх геохімічних властивостей були виявлені відмінності самоочисної здатності ландшафтів. Порівняно високий потенціал винесення шкідливих речовин властивий підвищеним розчленованим ландшафтам південно- та північно-східної частин регіону. Найбільша частка площ із низьким потенціалом винесення забруднювальних речовин припадає на ландшафти Дніпровсько-Деснянського Полісся та Північної області Дніпровської терасової рівнини. Антропогенний вплив на довкілля Чернігівського краю є досить значним і різноманітним за видами, інтенсивністю та територіальним поширенням. Наслідками цього впливу є радіаційне забруднення західної та північно-східної частин регіону, високі рівні забруднення атмосферного повітря у містах, незадовільний екологічний стан ґрунтових вод насамперед Чернігівського Полісся, деградація земельних ресурсів. На основі аналізу екологічного стану окремих компонентів природи було визначено інтегральний показник забрудненості геосистем адміністративних районів (станом на 2019 р.) Чернігівської області та встановлено, що найвищим рівнем гостроти екологічної ситуації в регіоні вирізняються її західні та північно-східні території. У результаті проведення кореляційного аналізу між показниками забрудненості довкілля Чернігівщини та станом здоров’я населення було встановлено, що на захворюваність мешканців регіону найбільший вплив має радіаційне забруднення території 137Cs. Воно зумовлює високі показники захворюваності ендокринної системи, крові та кровотворних органів. Ця особливість має враховуватися при розробленні екологічної політики у регіоні.
Геоекологічний аналіз і оцінка території Чернігівської області
Keywords: геоекологічний аналіз; самоочисна здатність ландшафтів; антропогенне навантаження; забруднення ландшафтів; захворюваність населення; geoecological analysis; self-cleaning ability of landscapes; anthropogenic load; landscape pollution; population morbidity